Hit refresh : the quest to rediscover Microsoft's soul and imagine a better future for everyone - Nadella, Satya; Shaw, Greg (Microsoft executive); Nichols, Jill Tracie; Gates, Bill, 1955- (2017)
Microsoft's CEO tells the inside story of the company's continuing transformation and offers his vision for the coming wave of intelligent technologies. He examines how people, organizations, and societies can and must transform, how they must 'hit refresh' in their persistent quest for new energy, new ideas, and continued relevance and renewal. Yet he feels strongly that one of our essential qualities -- empathy -- will become ever more valuable. Satya Nadella also discusses his childhood in India and how he learned to lead along the way. He shares his meditations as sitting CEO -- one who is mostly unknown following the brainy Bill Gates and energetic Steve Ballmer. He explains how the company rediscovered its soul -- transforming everything from its culture to its business partnerships to the fiercely competitive landscape of the industry itself. Nadella concludes by introducing an equation to restore digital trust, ethical design principles, and economic growth for everyone.
Foreword / by Bill Gates -- From Hyderabad to Redmond: how Karl Marx, a Sanskrit scholar, and a cricket hero shaped my boyhood -- Learning to lead: seeing the Cloud through our Windows -- New mission, new momentum: rediscovering the soul of Microsoft -- A cultural renaissance: from know-it-alls to learn-it-alls -- Friends or frenemies?: build partnerships before you need them -- Beyond the Cloud: three shifts: mixed reality, artificial intelligence, and quantum computing -- The trust equation: timeless values in the digital age: privacy, security, and free speech -- The future of humans and machines: toward an ethical framework for AI design -- Restoring economic growth for everyone: the role of companies in a global society.
Includes bibliographical references (pages 247-255) and index.
Keywords: Nadella, Satya; Microsoft Corporation -- History; Microsoft Corporation -- Employees -- Biography; Chief executive officers -- United States -- Biography; Businessmen -- United States -- Biography; Computer software industry -- United States; Organizational change; Information society; Technology -- Social aspects; Empathy; Empathy; BIOGRAPHY & AUTOBIOGRAPHY -- Business; BUSINESS & ECONOMICS -- Corporate & Business History; BUSINESS & ECONOMICS -- Industries -- Computer Industry; Bestsellers, New York Times - Nonfiction; Biographies; Autobiographies; Autobiographies